IMPORTANCE OF DRIP IRRIGATION TECHNOLOGY IN COTTON GROWING (Academicia Globe: Inderscience Research, 2021)
This article presents the analytical results of the use of drip irrigation, starting with the current method of irrigation in the cultivation of cotton. The advantages of using drip irrigation in the efficient and rational use of water resources and the technology used in the cotton field are highlighted. Research has shown that the use of drip irrigation in cotton fields reduces water shortages, saves 31% compared to surface irrigation, increases productivity by 51.5%, ie 4.06 tons of cotton per hectare.During the season, drip irrigation provided 3510 m3 of water per hectare (12 irrigations), water productivity was 1.1 t / m3, saving 0.57 t / m3 of water compared to surface irrigation.